Multimodal linear endobronchial ultrasound guided mediastinal lymph node biopsy in the diagnosis of isolated mediastinal lymphadenopathy - Sze Shyang Kho; Chun Ian Soo; Mona Zaria Nasaruddin; Kah Wai Ngan; Jamalul Azizi Abdul Rahaman (Proceedings of Singapore Healthcare, 2022)
Isolated mediastinal lymphadenopathy represents a common diagnostic dilemma whereby morphological analysis of tissue specimens are frequently needed to ascertain the diagnosis. Cryobiopsy by linear endobronchial ultrasound (EBUS) guidance had recently been described in literature. We described a multimodality biopsy approach of a case of isolated tuberculous mediastinal lymphadenitis in which we employed the 22-gauge transbronchial aspiration needle, mini-forceps and a flexible cryoprobe sequentially. We aim to highlight the novel technique of linear EBUS guided cryobiopsy in acquiring superior histological specimen from mediastinal lymphadenopathy for diagnosis purposes. We also compared the histopathological quality of the specimens acquired from these three different biopsy modalities.